2023
DOI: 10.1007/s12144-023-04785-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of employment stress on college students: psychological well-being during COVID-19 pandemic in China

Abstract: Employment among final year college students in China has encountered unprecedented difficulties during the Coronavirus disease 2019 (COVID-19) pandemic, the high unemployment rate had led college graduates faced inadvertently mental health issues such as anxiety and depression. This study aims to investigate the impact of employment stress on college students' psychological well-being during the COVID-19 pandemic in China. An online survey consisting of demographic items (i.e., age, gender, subject major, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This accumulation of stressors can escalate physical and mental strain, potentially leading to severe health issues and psychological disturbances in extreme cases(?). Highlighting the importance of supporting students in their academic and professional endeavors as a means to promote mental well-being is crucial ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…This accumulation of stressors can escalate physical and mental strain, potentially leading to severe health issues and psychological disturbances in extreme cases(?). Highlighting the importance of supporting students in their academic and professional endeavors as a means to promote mental well-being is crucial ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Layoffs, salary cuts, and bankruptcies occur frequently and lead directly to a decrease in employment demand in the market and a reduction in employment opportunities for university students (Yang et al, 2022;Zheng et al, 2022). In this context, postponing employment by pursuing further study is a rational choice (Peng et al, 2023;Shi, 2023). Therefore, we propose the following hypothesis:Hypothesis 5:Social factors have a promoting effect on the intent to pursue an MD.…”
Section: Social Factors and The Intent To Pursue An MDmentioning
confidence: 99%
“…Previous studies have shown that good employment psychology can help mobilize college students’ strong learning motivation and improve their comprehensive ability to adapt to the employment environment in China ( Luciano et al, 2021 ; Senekal and Smith, 2022 ). In contrast, poor employment psychology affects college students’ thinking patterns and memory and reduces their employment competitiveness ( Jackson and Tomlinson, 2020 ; Wan Mohd Yunus et al, 2021 ; Peng et al, 2023 ). In summary, good employment psychology is of great significance in promoting the successful employment of rural college students.…”
Section: Introductionmentioning
confidence: 99%